(untitled) (Indian Journal of Public Health Research & Development, 2023)
Background: According to a report of WHO in 2007, 7% of world populations are carrier for Haemoglobin disorder and accurate and timely detection of various Hb variants including beta thalassemia trait can prevent occurrence of more serious disorders like thalassemia major in new-borns. But in a developing country like us use of high pressure liquid chromatography (HPLC) is limited, manual testing is done and accurate assessment is quite impossible. So, an observational cross-sectional study was done among 117 β-thalassemia and other Hemoglobinopathies cases and carriers. Objective: To find out the variation between the results of haematological tests obtained by automated counting chamber and manual method. Materials & Methods: This Observational, cross-sectional study was done at Thalassemia control unit and Physiology department of R G Kar Medical College and Hospital, Kolkata. β-thalassemia and other Hemoglobinopathies cases and carriers detected by complete blood count with HPLC from Thalassemia Outpatient Department (OPD) and antenatal mothers from antenatal clinic (ANC) were the population of this study. Findings and variations of the features of different hematological parameters amongst the β-thalassemia and other hemoglobinopathies were reviewed. A finding by HPLC was HbA, HbA2, HbF, HbD, and HbE. Results: Result of only Hb% obtained from HPLC and manual method was significantly different in β- THALASSEMIA Trait (p=0.0001), HbE Trait (p=0.0001), HbS trait (p=0.0001) and not significant in HbE disease and no other Red cell indices were significantly different in two methods. Conclusion: As hematological features like TC of RBC or PCV results by manual method shows no significant differences with HPLC/Automated counter assessment, such methods can be utilized even at primary level cost effectively for assessment of hematological disorders. But significant difference is seen in estimating Hemoglobin percentage in between Shalli‘s method and HPLC/Automated counter assessment. So some alternate method may introduce at lower level of health system other than Shalli’s method